The Role of Academic Information Systems in Supporting Educational Services Management - Pratama, Rafly Verdyansyah; Nor, Syariyan; Nashar, Joy (Green Publisher Indonesia, 2026)
Academic Information System (AIS) serves as a strategic digital infrastructure that supports educational service management in the digital transformation era. This study aims to analyze the role of AIS in improving educational service quality, enhancing academic administration efficiency, and increasing stakeholder satisfaction in higher education institutions. The study employed a descriptive quantitative research method using a survey approach involving 185 respondents consisting of students, lecturers, and administrative staff. Data were collected through a structured questionnaire using a 5-point Likert scale. Data analysis was conducted using descriptive statistics and Pearson correlation analysis. The results indicate that AIS implementation contributes positively to academic service efficiency, with an average user satisfaction score of 4.05 out of 5. Furthermore, a significant relationship was found between AIS feature availability and educational service quality (r = 0.742, p < 0.01). The data security dimension received the highest score (mean = 4.23), while the module integration dimension required further improvement (mean = 3.87). This study recommends continuous enhancement of system interoperability, user interface design, and human resource training to optimize AIS utilization in supporting effective educational service management.